Time required to initiate a defensive reaction to direct and feint attacks in fencing - Gutiérrez-Davila, M.; Javier Rojas, F.; Gutiérrez-Cruz, C.; Garcia, C.; Navarro, E. (Journal of Applied Biomechanics, 2016)
The two-fold purpose of this study was to analyze the time required by a fencer to initiate a defensive action in response to a direct attack, which involves identifying when the defending fencer detects the just-noticeable difference, and, secondly, to assess the effect that an attacker`s rapid armed hand movement (feint attack) has on the time required to initiate a defensive move. Twenty-four elite fencers and a fencing master were included in the study. Four adapted force plates were installed on a scaffold used as a fencing piste. A 3D video analysis system recorded the location of 2 markers installed on the fencing master`s shoulder and sword. The results confirm that the defending fencer has a mean movement time of 0.353 ± 0.028 s to perform the defensive action, which provides an advantage over the attacking fencer. The velocity of movement in the peripheral visual field has no influence on the time required by elite fencers to initiate a defensive action. This confirms the crucial role that response inhibition processes play when nonrelevant actions are perceived. Kinematic analysis of markers suggests that the eye movements of elite fencers are not the only source of information used while observing an attack.